Driving Behavior and mileage with the Incidence of ISPA in Students UNAIR Surabaya - Rezkha Mala Ludyaningrum (Jurnal Berkala Epidemiologi, 2016)
The World Health Organization states that air pollution contributes to 7 million deaths in the world each year. One of the health problems arising from air pollution is Upper Respiratory Tract Infection (URI/URTIs), which is known to rank first in the top ten diseases in 80% of Indonesia's provinces. This research was an observational analytic study using a case-control design. This research was conducted at the Health Service Center (PLK) of Universitas Airlangga in November 2015 - January 2016. The sampling technique used was systematic random sampling. The independent variables studied were driving behavior (usage of Personal Protective Equipment (PPE) and driving speed), and distance traveled, while the dependent variable was URTIs events. Primary data collection using interview techniques with questionnaire guidelines and secondary to the medical records of respondents. Data analysis used the chi-square statistical test. The results showed that there was a relationship between PPE usage (p = 0.008; OR = 2.6), average driving speed> 40km / hour (p = 0.001; OR = 5.4), and distance traveled <5 km (p = 0.001; OR = 5.156) with URTIs events. It was concluded that the use of PPE, driving behavior, and mileage are related to URTIs events so that PLK Universitas Airlangga officers provide brochures and counseling about the importance of using PPE and driving behavior to reduce the number of URTIs events.